2020
DOI: 10.1111/mmi.14451
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the ancillary pilus‐1 protein RrgA of Streptococcus pneumoniae on colonization and disease

Abstract: The Gram‐positive bacterium Streptococcus pneumoniae, the pneumococcus, is an important commensal resident of the human nasopharynx. Carriage is usually asymptomatic, however, S. pneumoniae can become invasive and spread from the upper respiratory tract to the lungs causing pneumonia, and to other organs to cause severe diseases such as bacteremia and meningitis. Several pneumococcal proteins important for its disease‐causing capability have been described and many are expressed on the bacterial surface. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
(109 reference statements)
1
10
0
Order By: Relevance
“…The importance of RrgA for brain infection is also supported by previous studies demonstrating that RrgA promotes bacterial entry into the brain from the blood-stream by interacting with the two endothelial receptors PECAM-1 and pIgR, and at autopsy, after a fatal pneumococcal meningitis, five out of six brains studied contained RrgA expressing pneumococci (Iovino et al, 2017). However, only about 20-30% of clinical pneumococcal isolates harbour the pilus-1 islet (Moschioni et al, 2010;Iovino et al, 2020).…”
Section: Discussionsupporting
confidence: 66%
“…The importance of RrgA for brain infection is also supported by previous studies demonstrating that RrgA promotes bacterial entry into the brain from the blood-stream by interacting with the two endothelial receptors PECAM-1 and pIgR, and at autopsy, after a fatal pneumococcal meningitis, five out of six brains studied contained RrgA expressing pneumococci (Iovino et al, 2017). However, only about 20-30% of clinical pneumococcal isolates harbour the pilus-1 islet (Moschioni et al, 2010;Iovino et al, 2020).…”
Section: Discussionsupporting
confidence: 66%
“…It was recently shown that Ply might facilitate the internalization of the pneumococcus into neurons together with the pilus-1, a protein complex with adhesin activity, exposed outside the cell wall, which has been associated with the capacity of pneumococci to interact with and invade different types of host cells (Iovino et al, 2020 ). More specifically, both the pilus-1 component RrgA and Ply interact with β-actin exposed on the neuronal plasma membrane.…”
Section: Neuronal Damage In Bacterial Meningitismentioning
confidence: 99%
“…However, pneumococcal proteins capable of binding collagen type VI have not been identified. In pneumococci, the presence of type‐1 pili has been associated with virulence and enhanced the ability to interact with epithelial and endothelial cells (Iovino et al, 2020). Proteins RrgA and RrgB were shown to be expressed along the entire pilus‐1 surface (Hilleringmann et al, 2008) and to consecutively interlock with collagen type I fibrils, as shown using atomic force microscopy (Becke et al, 2019).…”
Section: Discussionmentioning
confidence: 99%